2021
DOI: 10.3390/buildings11080371
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Sensitivity Analysis Method for Energy and Comfort Performance of an Office Building along the Chinese Coastline

Abstract: This study aimed to evaluate the comprehensive percentage influence of input parameters on building energy and comfort performance by a new approach of sensitivity analysis (SA) and explore the most reliable and neutral sampling and sensitivity assessment method. The research combined 7 sampling methods with 13 SA methods to comprehensively integrate the percentage influence of 25 input parameters on building energy and comfort performance in 24 coastal cities of China. The results have found that the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…where cov(x, y) represents the sample covariance of x and y, and var(•) represents sample variance. Mathematically, the Pearson correlation coefficient r xy takes values between −1 and 1 [42,43]. The larger the absolute value of r xy , the stronger it reveals the correlation between the variables.…”
Section: Lasso Regression Modelmentioning
confidence: 99%
“…where cov(x, y) represents the sample covariance of x and y, and var(•) represents sample variance. Mathematically, the Pearson correlation coefficient r xy takes values between −1 and 1 [42,43]. The larger the absolute value of r xy , the stronger it reveals the correlation between the variables.…”
Section: Lasso Regression Modelmentioning
confidence: 99%
“…This module is one of the most useful tools for parameterization that is coupled with the main software, and it is able to adjust the design parameters numerically or categorically. 92,93 Yi Zhang subsequently generated another software called JEPlus + EA to augment the software capabilities, which included the ability to perform optimization (NSGAII), 66,89,94 sensitivity analysis, [95][96][97] and a various of random sampling methodologies. 66,97,98 In present study, design variables are shading angle and shading distance to window edge, window height, and width.…”
Section: Design Of Variables and Objective Functionsmentioning
confidence: 99%
“…92,93 Yi Zhang subsequently generated another software called JEPlus + EA to augment the software capabilities, which included the ability to perform optimization (NSGAII), 66,89,94 sensitivity analysis, [95][96][97] and a various of random sampling methodologies. 66,97,98 In present study, design variables are shading angle and shading distance to window edge, window height, and width. 99 Objective functions are the amount of annual electricity generated by the solar shading and the annual electricity consumption of the building, which is intended to reduce.…”
Section: Design Of Variables and Objective Functionsmentioning
confidence: 99%
“…The results show that window visible transmittance, roof and wall solar absorptance, and phase change material thickness are the most sensitive parameters affecting energy consumption. Chen [20] and Gagnon [21] used two global sensitivity methods (regression and variance-based methods) and observed that the set-point temperature, the number of air changes, and the thermal parameters of roofs and windows were the most influential factors on the energy use of office buildings.…”
Section: Introductionmentioning
confidence: 99%